2022
DOI: 10.1155/2022/6790145
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Correlation of IgH‐CDR3 Immune Repertoire Diversity Test in Peripheral Blood of Neuromyelitis Spectrum Diseases

Abstract: Neuroretinitis spectrum disorder (NMOSD) is generally regarded as an acute or subacute inflammatory demyelinating disease of the central nervous system, mainly involving the optic nerve and spinal cord, mediated by humoral immunity. To address these questions, this work established an immunomic library of the heavy chain complementarity determinant 3 (gHI-CDR3) of peripheral blood lymphocyte B cell receptors. The library was established in patients with a spectrum of neurosyphilis-retinitis disorders. Six NMOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%